2012
DOI: 10.4012/dmj.2012-037
|View full text |Cite
|
Sign up to set email alerts
|

Effects of a convenient silica-coating treatment on shear bond strengths of porcelain veneers on zirconia-based ceramics

Abstract: Porcelain veneering of zirconia is necessary, but chipping of the veneer may cause clinical problems. We investigated the effects of silica coating to improve the bond strength between porcelain veneers and zirconia-based ceramics. The ceramics tested were zirconia/ alumina nanocomposites stabilized with ceria. Three surface treatments, grinding with a carborundum point (CA), sandblasting with alumina (SB), and Silano-Pen treatment (SP), were performed. Untreated specimens (NT) were examined as a control. The … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
29
0
1

Year Published

2013
2013
2022
2022

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 28 publications
(30 citation statements)
references
References 39 publications
0
29
0
1
Order By: Relevance
“…It has been shown that strong resin bonding to Y-TZP could be achieved by silica coating and silanization [2][3][4]13,17) .…”
Section: Effects Of Silica Coating Versus Alumina Sandblasting On Resmentioning
confidence: 99%
“…It has been shown that strong resin bonding to Y-TZP could be achieved by silica coating and silanization [2][3][4]13,17) .…”
Section: Effects Of Silica Coating Versus Alumina Sandblasting On Resmentioning
confidence: 99%
“…Os estudos observaram que o comportamento encontrado foi dependente do tipo de tratamento e tipo de cerâmica, porém, nem sempre havia uma melhora na união entre os materiais [21,[24][25][26][27][28]. Além disso, o uso de tratamentos que geram tensões na superfície da Y-TZP pode ser contraindicado devido à possível indução de transformação da fase tetragonal para monoclínica, que leva à degradação das suas propriedades mecânicas em baixas temperaturas (low temperature degradation -LTD) [6,7].…”
unclassified
“…Moreover, seldom cases of allergic reactions and MRI problems caused by zirconia ceramics have been reported. Besides, not only was zirconia used as a biomaterial find application in hip joint replacement 9) , it has also been highly used as a metal replacement for crowns, prostheses, brackets and implants 10,11) . However, as implants, zirconia shows morphological fixation with the surrounding tissues without producing any chemical or biological bonding 12) .…”
Section: Introductionmentioning
confidence: 99%